INTEGRATION ADAPTIVE NEURO FUZZY INFERENCE SYSTEM AND HYPOTHESIS TESTING IN CHICKEN EGG INVENTORY PREDICTION - Santosa, Sesar Husen; Hidayat, Agung Prayudha; Siskandar, Ridwan; Rizkiriani, Annisa (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2026)
Accumulation of egg stock in warehouses is currently the biggest problem of product loss due to damage to egg agents. This problem occurs partly because egg agents in Bogor cannot predict final inventory availability, so the number of egg orders exceeds storage capacity and is damaged due to being stored in the warehouse for too long. A prediction model for the final stock availability of eggs (crates) was developed. The prediction model for the final stock availability was based on the number of egg agents ordering from suppliers and the selling price of eggs using the Adaptive Neuro Fuzzy Inference System (ANFIS). The ANFIS model uses three variables: orders to suppliers, selling prices, and inventory, with 50 training data points and 30 testing data points, namely, orders to suppliers, selling prices, and inventory. Based on the results of training and testing data, it was found that the range of the Sugeno fuzzy model for the supplier order variable was 150 - 350 cases, and the selling price was IDR 24,000/kg - 29,500/kg with a fuzzy triangular membership set. The simulation results show testing and training data with epoch = 100 using fuzzy Sugeno, and the error value = 13.7. The results of the training model's determination test (R2) obtained a value of R² = 81.02%, and the testing model had a value of R² = 81.23%. The determination value (R²) above 80% indicate that the model is suitable for predicting the final stock amount for egg agents.